Identification of a pathogenic FTO mutation by next-generation sequencing in a newborn with growth retardation and developmental delay. Issue 3 (16th September 2015) - Daoud, Hussein; Zhang, Dong; McMurray, Fiona; Yu, Andrea; Luco, Stephanie M; Vanstone, Jason; Jarinova, Olga; Carson, Nancy; Wickens, James; Shishodia, Shifali; Choi, Hwanho; McDonough, Michael A; et al.
Abstract : Background: A homozygous loss-of-function mutation p.(Arg316Gln) in the fat mass and obesity-associated ( FTO ) gene, which encodes for an iron and 2-oxoglutarate-dependent oxygenase, was previously identified in a large family in which nine affected individuals present with a lethal syndrome characterised by growth retardation and multiple malformations. To date, no other pathogenic mutation in FTO has been identified as a cause of multiple congenital malformations. Methods: We investigated a 21-month-old girl who presented distinctive facial features, failure to thrive, global developmental delay, left ventricular cardiac hypertrophy, reduced vision and bilateral hearing loss. We performed targeted next-generation sequencing of 4813 clinically relevant genes in the patient and her parents. Results: We identified a novel FTO homozygous missense mutation (c.956C>T; p.(Ser319Phe)) in the affected individual. This mutation affects a highly conserved residue located in the same functional domain as the previously characterised mutation p.(Arg316Gln). Biochemical studies reveal that p.(Ser319Phe) FTO has reduced 2-oxoglutarate turnover and N -methyl-nucleoside demethylase activity. Conclusion: Our findings are consistent with previous reports that homozygous mutations in FTO can lead to rare growth retardation and developmental delay syndrome, and further support the proposal that FTO plays an important role in early development of human central nervous and cardiovascular systems.